321 Maintenance olaparib for BRCA-mutated ovarian cancer (OC) patients in 1st line and platinum-sensitive relapsed (PSR) settings: maximizing treatment opportunities. (18th September 2019) - Poveda, A; Sackeyfio, A; Friedlander, M
Abstract : Objectives: In Phase III randomized trials, maintenance therapy with the PARP inhibitor olaparib demonstrated a significant benefit versus placebo in BRCA-mutated advanced OC patients who had a complete/partial response to platinum-based chemotherapy (PBC) in newly diagnosed (SOLO1; NCT01844986 ) and PSR (SOLO2/ENGOT-Ov21; NCT01874353 ) settings. We investigate missed opportunities for maintenance olaparib in relapsed settings. Methods: Published response rates to PBC in newly diagnosed BRCA-mutated advanced OC are scarce. These are estimated by applying a BRCA response rate factor determined from a population-based study (Alsop et al) to expected PBC response rates in newly diagnosed high grade serous OC (75%). For BRCA-mutated PSR OC, response to second-line PBC was 64.6% (Alsop et al). Platinum sensitivity for second-line PBC eligibility was determined from placebo patients in SOLO1 remaining progression free after 6 months (80.6%). Results: In newly diagnosed and PSR settings, predicted proportions of eligible patients for olaparib are 84% and 44%, respectively (table 1 ). Missed treatment opportunities in PSR settings are likely due to platinum resistance and non-response to second-line PBC. Approximately 48% of patients could miss the opportunity to benefit from PARP inhibitor maintenance if untreated in the first line. Conclusions: Earlier olaparib therapy provides the chance of long-term remission and prevents patients missing opportunities for second-line PARP inhibitor maintenance due to platinum resistance or non-response to PBC. Disease burden associated with multiple chemotherapy lines in advanced settings is also reduced or delayed.